2017
DOI: 10.1002/jclp.22508
|View full text |Cite
|
Sign up to set email alerts
|

Finding a Trans‐Affirmative Provider: Challenges Faced by Trans and Gender Diverse Psychologists and Psychology Trainees

Abstract: This article explores some of the challenges faced by trans and gender diverse (TGD) individuals who not only are attempting to access trans-affirmative care, but who are also members of the very profession from which they are seeking services. The authors explore challenges related to finding supervision, accessing care for assessment services, and finding a provider for personal counseling. With each example, the authors unpack the challenges and also address the implications for training for all involved. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Previous research in Australia has highlighted issues relating to staff inexperience with TGD health (Hyde et al, 2014). This is likely a reflection of the individual’s lack of education in the area (Dickey and Singh, 2017). Even mental health professionals who view themselves as competent in TGD health may sometimes use inappropriate language (Whitman and Han, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in Australia has highlighted issues relating to staff inexperience with TGD health (Hyde et al, 2014). This is likely a reflection of the individual’s lack of education in the area (Dickey and Singh, 2017). Even mental health professionals who view themselves as competent in TGD health may sometimes use inappropriate language (Whitman and Han, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Cultivating collaborative environments where students can be involved in TGD inclusivity efforts that are a part of broader shared program goals promotes transparency and encourages sustainable change. These issues with lack of training, accompanied by the high levels of marginalization that TGD graduate students experience (Dickey & Singh, 2017a; Goldberg et al, 2021; Knutson et al, 2022), make it essential to engage in educational initiatives and reflection to address the biases embedded in most programs.…”
Section: Takeaway Points Related To Training Sites and Tgd Inclusivitymentioning
confidence: 99%
“…In addition, trans and nonbinary people often experience gender-based discrimination and violence in their lives (American Psychological Association [APA], 2015). For example, Dickey and Singh (2017) found that trans-specific discrimination can lead to concealment of trans identity, internalization of trans-negative beliefs and attitudes, and anticipation of anti-trans discrimination. Such experiences can lead to negative health outcomes including suicide, depression, anxiety, eating disorders, and substance abuse (Dickey & Singh, 2017; Dickey et al, 2017; Velez et al, 2016; White Hughto et al, 2017).…”
Section: The Present Studymentioning
confidence: 99%
“…For example, Dickey and Singh (2017) found that trans-specific discrimination can lead to concealment of trans identity, internalization of trans-negative beliefs and attitudes, and anticipation of anti-trans discrimination. Such experiences can lead to negative health outcomes including suicide, depression, anxiety, eating disorders, and substance abuse (Dickey & Singh, 2017; Dickey et al, 2017; Velez et al, 2016; White Hughto et al, 2017). Thus, traditional gender socialization practices, informed by traditional gender ideologies, can be particularly harmful for trans and nonbinary individuals.…”
Section: The Present Studymentioning
confidence: 99%